Monitoring open dumping of municipal waste in Gujranwala, Pakistan using a combination of satellite based bio-thermal indicators and GIS analysis. (December 2019) - Mahmood, Khalid; Ul-Haq, Zia; Faizi, Fiza; Tariq, Salman; Naeem, Muhammad Azhar; Rana, Asim Daud
Highlights: An addition to the effective use of satellite data for studying MSW dumps. Extended time scale has helped understanding growth of influenced zone around dump. Indicator of assessing procedural stability of observations has been developed. Bio-thermally influenced zone has a direct relation with amount of dumped waste. Ambient temperature and dry weather conditions control size of the influence zone. Abstract: This study explores use the of remotely sensed satellite data for monitoring environmental impact of MSW open dumps on their surroundings using bio-thermal indicators. The study has made use of 66 images of Lansat-8 from January 2014 to December 2017, to monitor main MSW dump of Gujranwala, Pakistan. On average thermally influence zone of the dump has been found extended to 480 m around it. Whereas the seasonal average radius of the influence in the zone is measured as 375 m, 425 m, 450 m, 527 m, 590 m and 600 m for spring, monsoon, wet summer, winter-II, winter-I and dry summer respectively. Extreme temperatures and dry weather conditions increase the range of the zone. The range of the bio-influence zone around the dump has been measured using satellite driven VIs of MSAVI, SAVI and NDVI that averages to 590 m. The seasonal averages measured by averaging results from all three VIs are 326 m, 410 m, 430 m, 620 m, 692 m and 1100 m for spring, monsoon, winter-II, wet summer, winter-I and dry summer respectively. In addition, max-min gap of the measurements has been used to assess operational stability of individual parameters and seasons for the used spatial analysis. Development of bio-thermally influence zone with time and a comparison with previous studies a positive correlation between measured range of bio-thermal influence zone and amount of MSW dumped at sites has been verified.